Inequities in childhood cancer research: A scoping review - Jean Hunleth; Sarah Burack; Lindsey Kaufman; Caroline Mohrmann; Thembekile Shato; Eric Wiedenman; Janet Njelesani (EJC Paediatric Oncology)
An integral part of understanding and then designing programs to reduce childhood cancer inequities includes adequate representation of people with cancer in research, including children. A scoping review was carried out to understand how cancer research is oriented toward inequities and to identify who has participated in childhood qualitative cancer research. A systematic search identified 119 qualitative studies that met inclusion criteria, with most studies taking place in high-income countries (n=84). Overall, data were lacking on social determinants of health at multiple levels—structural, household, child, and guardian. Only 29 studies reported on race and/or ethnicity, with the majority of those including predominantly or all white children. Six articles included socioeconomic information, and across most articles, attention was absent to the financial ramifications of cancer care. Limited reporting of sociodemographics highlights a broader issue of neglecting key demographics and social factors that contribute to inequities.